Fixed or Floating Exchange Regimes : Does it Matter for Inflation? - Quirk, Peter (Washington, D.C. : International Monetary Fund, 1994)
This paper reviews recent experience with the choice of floating or fixed ('anchor') exchange regimes in industrial and developing countries. It concludes that desirable differences between the two sets of regimes have narrowed, owing to the useful operational role of exchange rate margins and unavoidable medium-term rate adjustments in the context of fixed regimes. A survey of recent empirical cross-country literature also suggests little unambiguous association of the choice of exchange regime with macroeconomic performance, inflation in particular. Stability of the exchange rate has generally been a by-product of other policy choices. Even announcement effects of the regime on inflation-fighting credibility depend on the country-specific assignments of policy instruments to more than one institution--central bank, government, or regional and multilateral institutions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet